ANALISIS KESIAPAN GURU DALAM PENERAPAN DEEP LEARNING UNTUK MENINGKATKAN KREATIVITAS SISWA - Nur Azura Azura; Haifaturrahmah Haifaturrahman; Nursina Sari Nursina Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze teacher readiness in implementing deep learning to enhance student creativity as one of the key competencies of the 21st century. The research method used is descriptive qualitative with data collection techniques through questionnaires, interviews, and observations of teachers directly involved in the learning process. The results show that teacher readiness is in the fairly good category, especially in terms of theoretical understanding of deep learning, but there are still variations in practical application, especially in designing project-based learning, utilizing digital technology, and classroom management that supports student creativity. The main challenges faced by teachers include limited time, facilities, and a lack of relevant training.